Vigilance and vengence : NGOs preventing ethnic conflict in divided societies - Rotberg, Robert I. (Cambridge : The World Peace Foundation, 1996)
With Brookings Institution Press
Keywords: Culture conflict -- Prevention; Ethnic relations; Non-governmental organizations; Social conflict -- Prevention